THE MAIN ASPECTS OF INNOVATIVE DEVELOPMENT REGIONS OF THE REPUBLIC OF UZBEKISTAN - Abdullaevich, Otajanov Umid (Journal of process management and new technologies, 2019)
The article considers the main problems of the development of innovative activities of the regions of Uzbekistan, focuses on the policy of the government of the republic on this issue, and suggests measures to further solve them, shows the possibility of using neural network technologies in modeling regional development based on classical statistical and econometric methods.